Primary treatment for oropharyngeal squamous cell carcinoma in Alberta, Canada: A population‐based study. Issue 11 (7th August 2017) - Hobbs, Amy J.; Brockton, Nigel T.; Matthews, T. Wayne; Chandarana, Shamir P.; Bose, Pinaki; Guggisberg, Kelly; Fick, Gordon H.; Dort, Joseph C.
Abstract: Background: The incidence of human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (SCC) is increasing and has better survival than non‐HPV related oropharyngeal SCC. This study compared surgical to nonsurgical treatments and demographic, clinical, and survival differences in patients with oropharyngeal SCC, stratified by p16 status. Methods: We assembled a cohort of adult patients with oropharyngeal SCC diagnosed between 2000 and 2008 in Alberta. The tumor p16 biomarker was measured using fluorescent immunohistochemistry. Results: In this cohort, p16 data were available for 115 of 357 patients; and 66% (n = 76) were p16‐positive. Patients with p16 data had comparable outcomes to those without. Surgically treated p16‐negative patients had improved 5‐year disease‐specific survival (DSS) and overall survival (OS) compared with nonsurgical patients. There were no differences in survival outcomes between surgical and nonsurgical treatment for patients with p16‐positive disease. Conclusion: Patients with p16‐positive oropharyngeal SCC had similar outcomes regardless of treatment. Patients with p16‐negative tumors may benefit from primary surgery with postoperative adjuvant therapy.